New Attorney Swearing In Ceremony Held in State Building Auditorium - Watkins, Howard::::::::: (1986)
State Bar District 5 Governor Dennis Cornell with Marc Feldman and his wife Marc Feldman was 5th Executive Director of Fresno-Merced Counties Legal Services